Essays on Indian economy/ by V. K. Agarwal and P.K. Jain - "Agarwal, V. K." (New Delhi, 1990)
The book includes number of essays both from the economic and social angles. These essays have been mainly devoted to the topics relating to labour problems, large scale industries, economic planning, and other economic and social problems.
Keywords: Economics